Comparação entre técnicas para caracterização extrínseca de cerâmicas em cad/cam - Oliveira, Pâmella Tomazi Godoy de (2022)
Objective: The present study aims to evaluate the roughness and color stability of lithium disilicate and leucite ceramics after brushing cycling. Materials and Methods: 84 ceramic blocks (1.0 cm x 1.0 cm) were produced in lithium disilicate and leucite and divided into 3 groups, according to the post-machining technique used: group 1: polished ceramic (negative control) (NC); group 2: stain (pigmented) ceramic followed by glaze, according to the manufacturer's recommendations (positive control) (PC); group 3: simultaneous staining with glaze (alternative technique) (TE). The change in gloss and surface roughness was evaluated at 4 different times, after the simulated brushing test. Results: The results of the multivariate tests showed that there was a triple interaction effect between the material, treatment and time factors on the average roughness (p< 0.001) and luminosity (p value < 0.05). There was no statistically significant difference in the mean roughness in the NC and TE groups for the leucite and lithium disilicate samples, but there was an increase in the mean roughness at t1 in the CP and TE groups. Regarding the results of luminosity in the comparison within the materials and times, there was a statistically significant difference in the leucite samples in the CP group in relation to the others. The CN and TE groups did not differ statistically from each other. Conclusion: There was equal color stability in samples from all groups tested on leucite-based ceramics over time. In lithium disilicate ceramics, there was a reduction in luminosity in the polishing group. In leucite-based ceramics, the average roughness obtained an intermediate position in the experimental technique in relation to the polishing group and the pigment and glaze group at all times. In lithium disilicate ceramics, the experimental technique group showed similar roughness to the pigment and glaze. Clinical Relevance: TE showed similar color stability and intermediate roughness in relation to the other groups and a less rough surface over time after the simulated brushing cycles, in relation to the CP group.